2014
DOI: 10.1371/journal.pone.0098164
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Assessment of Reference Genes for Quantitative PCR Normalization in Migratory Locust Locusta migratoria (Orthoptera: Acrididae)

Abstract: Locusta migratoria is a classic hemimetamorphosis insect and has caused widespread economic damage to crops as a migratory pest. Researches on the expression pattern of functional genes in L. migratoria have drawn focus in recent years, especially with the release of genome information. Real-time quantitative PCR is the most reproducible and sensitive approach for detecting transcript expression levels of target genes, but optimal internal standards are key factors for its accuracy and reliability. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 75 publications
3
39
0
Order By: Relevance
“…Previous reference gene validation studies combined high and low temperature treatments, collectively referring to them as temperature treatment [18] , [27] , [40] , [41] . Interestingly, we found that the gene rankings for high and low temperature were different ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reference gene validation studies combined high and low temperature treatments, collectively referring to them as temperature treatment [18] , [27] , [40] , [41] . Interestingly, we found that the gene rankings for high and low temperature were different ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of cDNA and RT‐qPCR analysis were performed following previously described methods (Zhao et al ., ). Relative mRNA levels of target genes were calculated using the 2 −∆∆Ct method by normalizing to the expression of the internal marker gene ribosomal protein L32 , which exhibited the most stable expression at different stages and in different tissues (Livak and Schmittgen, ; Yang et al ., ). The primer information for each gene is listed in Table S2.…”
Section: Methodsmentioning
confidence: 97%
“…) and Locusta migratoria (Yang et al . ). α‐Tubulin , a type of cytoskeletal structure protein, is another commonly used reference gene.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, our results show that Actin was the most stable reference gene in temperature experiments. It has been reported that, when suffering from different temperature treatments and starvation, Actin was selected as a stable reference gene in Myzus persicae (Kang et al 2017) and Locusta migratoria (Yang et al 2014). α-Tubulin, a type of cytoskeletal structure protein, is another commonly used reference gene.…”
Section: Discussionmentioning
confidence: 99%